POTENSI PENGEMASAN MAKANAN TRADISIONAL ROTI TENONK SEBAGAI SOUVENIR DI PASAR KULINER PADANG PANJANG - Oktoudis, Tenggo; Asnur, Lise (Komunitas Manajemen Kompetitif, 2024)
This research originated from the researcher's observation of the packaging of Tenonk Bread in the Padang Panjang Culinary Market which still uses snack box packaging which results in a short expiration period and causes a decrease in the quality of food taste. The method used is descriptive method with qualitative data using snowball sampling technique. The results in the study are in improving the quality of Roti Tenonk Padang Panjang packaging. Roti Tenonk Padang Panjang must develop product packaging that is not only resistant to external contamination, but also practical packaging, and does not cause a decrease in food quality. In increasing the attractiveness of Roti Tenonk Padang Panjang product packaging, the owner of Roti Tenonk must improve the quality of materials and add other colors to attract consumers' attention. Information regarding the size or weight of the packaging and other additional information on the packaging must be included. Keywords: Potential, Packaging, Traditional Food, Tenonk Bread, as Souvenir in Padang Panjang Culinary Market